Effect of alcohol consumption on haemoglobin level among non-pregnant reproductive age women in Ethiopia: a cross-sectional secondary data analysis of the 2016 Ethiopian Demographic Health Survey - Melese Linger Endalifer; Gedefaw Diress (BMJ Open)
Objective The aim of this study was to assess the effect of alcohol consumption on haemoglobin levels among non-pregnant reproductive age women using national representative data.Method A secondary data analysis was conducted using data from the 2016 Ethiopia Demographic and Health Survey. The main outcome of interest was anaemia defined as a haemoglobin value <12 g/which was measured using HemoCue, and adjusted for both altitude and smoking status. The main exposure variable was alcohol consumption. Both multivariable logistic regression and generalised linear model were employed to assess the association between alcohol consumption and anaemia and to compare the mean of haemoglobin between the non-drinkers and three alcohol consumption frequency categories, respectively, after adjusting for the potential confounders.Result In the current analysis, a total of 13 436 non-pregnant women were included. The overall prevalence of anaemia among non-pregnant women was 23.2% of which 17.9% were mildly anaemic, 4.6% were moderately anaemic and 0.7% were severely anaemic. There was a significant negative association between anaemia and respondents’ history and frequency of alcohol consumption in the pooled sample. Among non-pregnant women, the odds of having anaemia were decreased with a history of alcohol drinking (adjusted OR (AOR)=0.32 (95% CI: 0.214 to 0.394)). Women who drunk alcohol less than once a week ((AOR=0.54 (95% CI: 0.31 to 0.94), those who drunk alcohol at least once a week (AOR=0.50 (95% CI: 0.28 to 0.88)) and who drunk alcohol almost every day in the last 12 months (AOR=0.42 (95% CI: 0.21 to 0.81)) had significantly lower odds of having anaemia than women who had not ever taken a drink that contain alcohol.Conclusion This study showed that nearly a quarter of non-pregnant women in Ethiopia were found to be anaemic. Alcohol consumption increases haemoglobin concentration. Further cohort or experimental studies are therefore needed to further assess the relationship between alcohol consumption and haemoglobin level among Ethiopian populations.